2016
DOI: 10.1007/s10640-016-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Management Hinders Coastal Climate Adaptation: The Spatial-dynamics of Beach Nourishment

Abstract: Climate change threatens to alter coastline erosion patterns in space and time and coastal communities adapt to these threats with decentralized shoreline stabilization measures. We model interactions between two neighboring towns, and explore welfare implications of spatial-dynamic feedbacks in the coastal zone. When communities are adjacent, the community with a wider beach loses sand to the community with a narrower beach through alongshore sediment transport. Spatial-dynamic feedbacks create incentives for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…This suggests that, in addition to getting redistributed across the shoreface, if some nourishment sand is redistributed laterally by wave-driven gradients in alongshore sediment transport, neighboring coastal communities may benefit from each other's nourishment investments (Lazarus, McNamara, et al, 2011). A community that does not invest in beach nourishment may still benefit from the beach nourishment projects of its neighbors-in resource economics, a dynamic related to the 10.1029/2018EF001070 prisoner's dilemma known as "free-riders" and "suckers" (Gopalakrishnan, McNamara, et al, 2016;Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, in addition to getting redistributed across the shoreface, if some nourishment sand is redistributed laterally by wave-driven gradients in alongshore sediment transport, neighboring coastal communities may benefit from each other's nourishment investments (Lazarus, McNamara, et al, 2011). A community that does not invest in beach nourishment may still benefit from the beach nourishment projects of its neighbors-in resource economics, a dynamic related to the 10.1029/2018EF001070 prisoner's dilemma known as "free-riders" and "suckers" (Gopalakrishnan, McNamara, et al, 2016;Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, involuntary rural-urban migration often replaces one set of risks with another, especially when urban destinations are poorly equipped to provide basic human necessities to the new migrants. Thus, migrants affected by climate change at their places of origin may become exposed to a second level of stress at urban destinations, where new hazards may reinforce existing vulnerabilities (McNamara et al 2016).…”
Section: Impacts On Human Settlement and Livelihoods: Rural-urban Migrationmentioning
confidence: 99%
“…Hard protection methods also require routine maintenancein fact, countries across the globe are enhancing their hard-engineered structures, such as levees and dikes, to accommodate climate change-induced flooding (Harman et al 2015;Deltacommissie 2008;Ligtvoet et al 2012); yet, as demonstrated by Schmidt et al (2013), stakeholders gravitate toward hard protection measures over other adaptation alternatives. Highly developed or tourist-oriented coastlines greatly contribute to a coastal community's economy, and constructing hard defense structures leaves the coastline relatively unaltered from its current, highly attractive statean explanation for the observable, global preference for this adaptation method.…”
Section: Coastal Adaptation As a Community Planning Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a beach nourishment (beach extension/ construction) project that creates a subtle seaward bump in the shoreline can increase the rates of net sediment delivery to adjacent beaches. When towns implement localized stabilization policies, not accounting for the physical and economic implications of these dynamic spatial interactions, it results in suboptimal outcomes relative to coordinated management of the coastline (Gopalakrishnan et al, 2014).…”
Section: Alongshore Connections: Communities Affect Each Othermentioning
confidence: 99%